PENGARUH CITRA MEREK, KEPERCAYAAN (TRUST) DAN KOMITMEN TERHADAP LOYALITAS NASABAH PADA PT. HENAN PUTIHRAI ASSET MANAGEMENT - Siti Maliyah (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
This research discusses the influence of brand image, confidence (trust) and a commitment to customer loyalty at PT. Henan Putihrai Asset Management. Authors limit the scope of the problem only in Jl. Jenderal Sudirman, Jakarta. Data were obtained through questionnaires to 131 Responden.PT. Henan Putihrai Asset Management. Data collection methods used are convience sampling, whereas analytical tool used is structural equation model SEMAMOS 18. Results of hypothesis testing showed significant influence on customer loyalty commitment, but partially not affect the brand image segnifikan of trust, brand image segnifikan no effect on commitment, and trust segnifikan no effect on commitment. For further research it is advisable to do some research other than a company engaged in the investment manager. Keywords: brand image, confidence (trust), commitment, customer loyalty